2022
DOI: 10.1097/gme.0000000000002016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the association between amino acid and acylcarnitine profiles and different levels of coronary artery disease risk in postmenopausal women using targeted metabolomics technique

Abstract: Objectives: Postmenopausal women are at increased risk of developing coronary artery disease (CAD). Metabolomic approaches aim at discovering more helpful biomarkers of CAD to reduce the disease burden in the future. Here, we intend to find potential blood biomarkers, amino acids, and acylcarnitines in postmenopausal women with different severity of CAD by using high-throughput methods.Method: This cross-sectional study was performed on postmenopausal women (n = 183) who underwent coronary CT scans. Coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…As all of our subjects had well-controlled and conservatively treated T2D, though, changes in acylcarnitines were specific to metformin treatment. Circulating acylcarnitines have been identified as correlating with CVD morbidity and mortality (Hosseinkhani et al, 2022;Paulin Beske et al, 2022;Storesund et al, 2022). Our results suggest metformin has beneficial effects on these outcomes independent of T2D disease status.…”
Section: Metabolites Associated With Cvd Risk Are Reduced With Metfor...mentioning
confidence: 58%
“…As all of our subjects had well-controlled and conservatively treated T2D, though, changes in acylcarnitines were specific to metformin treatment. Circulating acylcarnitines have been identified as correlating with CVD morbidity and mortality (Hosseinkhani et al, 2022;Paulin Beske et al, 2022;Storesund et al, 2022). Our results suggest metformin has beneficial effects on these outcomes independent of T2D disease status.…”
Section: Metabolites Associated With Cvd Risk Are Reduced With Metfor...mentioning
confidence: 58%
“…This condition is closely linked to dyslipidemia and diabetes. Menopause, for women, is a distinctive period characterized by a higher incidence of various chronic complications, dyslipidemia, diabetes, and other diseases compared to men [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Ganna et al identified four lipid-related metabolites with evidence for clinical utility, as well as a causal role in CHD development. 1 Hosseinkhani et al (11) observed that levels of circulating amino acids and acylcarnitines were partially correlated with CHD severity in postmenopausal women. Würtz et al substantiates the value of high-throughput metabolomics for biomarker discovery and improved risk assessment.…”
Section: Introductionmentioning
confidence: 99%